2005
DOI: 10.1177/07419325050260030101
|View full text |Cite
|
Sign up to set email alerts
|

The Current State(s) of Prereferral Intervention Teams

Abstract: Current prereferral intervention team (PIT) regulations, prevalence, membership, goals, and intervention information from two national telephone surveys are reported. Survey 1 obtained information about state PIT regulations and recommendations from employees of the 51 state education departments (50 states and Washington, DC). Survey 2 obtained information about elementary schools' PIT prevalence, membership, goals, and common intervention recommendations from employees of 200 elementary schools (4 per state)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…The results of this study are similar to previous research (e.g., Slonski-Fowler and Truscott 2004;Truscott et al 2000) that suggests teachers are interested in making instructional changes and providing classroom-based interventions to students who need additional assistance. Although many participants reported frustration over demands to use data without instruction in how to do so, and had low levels of confidence in their ability to use available assessment data for instructional purposes prior to the PD provided in this project, our participants were interested in understanding how to effectively incorporate assessment data into their instructional practices.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study are similar to previous research (e.g., Slonski-Fowler and Truscott 2004;Truscott et al 2000) that suggests teachers are interested in making instructional changes and providing classroom-based interventions to students who need additional assistance. Although many participants reported frustration over demands to use data without instruction in how to do so, and had low levels of confidence in their ability to use available assessment data for instructional purposes prior to the PD provided in this project, our participants were interested in understanding how to effectively incorporate assessment data into their instructional practices.…”
Section: Discussionsupporting
confidence: 87%
“…In this chapter, we have provided a review of best practices for school teams as identifi ed in the teaming literature and have proposed a model for team functioning (GTO) that can be used to ensure quality service implementation and sustainability. While we are hopeful that teams are able to benefi t from the information in this chapter, we recognize the fact that very few school teams currently incorporate these types of procedures into their routine practices (Truscott et al, 2005 ). Thus, there is still work to be done to bridge the gap between science and practice in order to make evidence-based team functioning a reality.…”
Section: Discussionmentioning
confidence: 98%
“…Despite these benefi ts, however, research indicates teams must be well implemented to achieve outcomes and realize their goals (Kovaleski et al, 1999 ;Truscott, Cohen, Sams, Sanborn, & Frank, 2005 ). In a study of multi-district implementation of instructional support teams (ISTs), Kovaleski and colleagues ( 1999 ) demonstrated that students in schools with instructional support teams had higher academic performance than control schools, but only for schools that implemented the team problem-solving process to a high degree.…”
Section: Benefi Ts Of School Teamsmentioning
confidence: 99%
“…The RTI (problem solving) team is usually comprised of specialized teachers and a school administrator who collaborate and consult with the classroom teacher to enhance the teacher's competence and skills. The purpose of the team's problem-solving involvementis to provide nonspecial education intervention for children who are struggling academically, before the child is referred for special education (Tam and Heng 2005;Truscott et al 2005). …”
Section: What Is Rti?mentioning
confidence: 99%
“…In Tier II private tutoring might be done by a specialized teacher or a general education teacher (Truscott et al 2005). At each tier of intervention students who show slow or no progress are moved to the subsequent tiers of intervention to receive individual instruction in higher frequency.…”
Section: Tier IImentioning
confidence: 99%